1992
DOI: 10.1159/000110903
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Ischemic Stroke: A Case Control Analysis

Abstract: Case control analysis of 204 patients with acute ischemic stroke revealed the matched pair odds ratio (and 95% confidence limits) for hypertension, ECG abnormality, heart disease of any type, diabetes, smoking and alcohol intake to be 3.95 (2.5, 6.2), 2.1 (1.4, 3.1), 2.1 (1.4, 3.2), 1.7 (1.1, 2.6), 1.8 (1.1, 2.8) and 1.5 (0.86, 2.6), respectively. Except alcohol intake, the other factors were statistically significant. Hemoglobin, packed cell volume (hematocrit), serum cholesterol, triglycerides and low-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 7 publications
3
38
1
1
Order By: Relevance
“…2 In our study, we found that diabetes is mainly a risk factor for ischemic stroke as supported by previous studies. 4,15,32 In our study obesity was less (10.4%) as against 22.3% in Fabry study. 10 Obesity, both general and abdominal is associated with higher risk of stroke, which may be the cause of increased incidence of stroke in women 10 Dyslipidemia is an important risk factor for stroke in previous studies4, 10, 28, which is also shown in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…2 In our study, we found that diabetes is mainly a risk factor for ischemic stroke as supported by previous studies. 4,15,32 In our study obesity was less (10.4%) as against 22.3% in Fabry study. 10 Obesity, both general and abdominal is associated with higher risk of stroke, which may be the cause of increased incidence of stroke in women 10 Dyslipidemia is an important risk factor for stroke in previous studies4, 10, 28, which is also shown in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Three decades of research of this topic have yielded inconsistent results [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and have led to sharply opposing viewpoints about the importance of circulating cholesterol in ischemic stroke. 10,20 -24 At least part of the controversy can be attributed to methodological shortcomings of previous work.…”
mentioning
confidence: 99%
“…16,17 Isolated systolic hypertension is also correlated with increased thickness and plaque formation of the internal carotid artery. 18 In our study, hypertension was most common risk factor (80%) followed by diabetes mellitus (60%). Chronic hypertension promotes atherosclerosis.…”
Section: Discussionmentioning
confidence: 51%